Design, Synthesis, and Anticancer and Antibacterial Activities of Quinoline-5-Sulfonamides - Zieba, Andrzej; Pindjakova, Dominika; Latocha, Malgorzata; Plonka-Czerw, Justyna; Kusmierz, Dariusz; Cizek, Alois; Jampilek, Josef (Molecules (Basel, Switzerland), 2024)
A series of new unique acetylene derivatives of 8-hydroxy- and 8-methoxyquinoline- 5-sulfonamide 3a-f and 6a-f were prepared by reactions of 8-hydroxy- and 8-methoxyquinoline- 5-sulfonyl chlorides with acetylene derivatives of amine. A series of new hybrid systems containing quinoline and 1,2,3-triazole systems 7a-h were obtained by reactions of acetylene derivatives of quinoline-5-sulfonamide 6a-d with organic azides. The structures of the obtained compounds were confirmed by 1H and 13C NMR spectroscopy and HR-MS spectrometry. The obtained quinoline derivatives 3a-f and 6a-f and 1,2,3-triazole derivatives 7a-h were tested for their anticancer and antimicrobial activity. Human amelanotic melanoma cells (C-32), human breast adenocarcinoma cells (MDA-MB-231), and human lung adenocarcinoma cells (A549) were selected as tested cancer lines, while cytotoxicity was investigated on normal human dermal fibroblasts (HFF-1). All the compounds were also tested against reference strains Staphylococcus aureus ATCC 29213 and Enterococcus faecalis ATCC 29212 and representatives of multidrug-resistant clinical isolates of methicillin-resistant S. aureus (MRSA) and vancomycin-resistant E. faecalis. Only the acetylene derivatives of 8-hydroxyquinoline-5-sulfonamide 3a-f were shown to be biologically active, and 8-hydroxy-N-methyl-N-(prop-2-yn-1-yl)quinoline-5-sulfonamide (3c) showed the highest activity against all three cancer lines and MRSA isolates. Its efficacies were comparable to those of cisplatin/doxorubicin and oxacillin/ciprofloxacin. In the non-cancer HFF-1 line, the compound showed no toxicity up to an IC50 of 100 µM. In additional tests, compound 3c decreased the expression of H3, increased the transcriptional activity of cell cycle regulators (P53 and P21 proteins), and altered the expression of BCL-2 and BAX genes in all cancer lines. The unsubstituted phenolic group at position 8 of the quinoline is the key structural fragment necessary for biological activity.
Keywords: Microbial Sensitivity Tests; Staphylococcus aureus; Enterococcus faecalis; 1,2,3-triazole; Humans; acetylene derivatives; antibacterial activity; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; synthesis; sulfonamidy; Antineoplastic Agents; mikrobiální testy citlivosti; Quinolines; lidé; antibakteriální látky; molekulární struktura; Drug Design; Molecular Structure; anticancer activity; Anti-Bacterial Agents; racionální návrh léčiv; nádorové buněčné linie; protinádorové látky; cytotoxicity; Cell Line, Tumor; 8-hydroxyquinoline; Sulfonamides; chinoliny